Food insecurity and malnutrition in vulnerable households with children under 5 years on the Ecuadorian coast: a post-earthquake analysis - Maria Herrera-Fontana; Aida Maribel Chisaguano; Valeria Villagomez; Luzdary Pozo; Mónica Villar; Nancy Castro; Pablo Beltran (James Cook University, 2020)
Introduction: A household's nutritional status and food security can be affected after a natural disaster, especially in families who live in risk situations. The objective of this study was to determine the prevalence of food insecurity, inadequate dietary diversity and poor nutritional status of mothers and children under 5 years old from vulnerable families residing in the rural community of La Punta, after the earthquake in Ecuador on 16 April 2016. Methods: Through a non-probabilistic sampling, 28 families were selected. The levels of food insecurity in households were determined by applying a food safety scale and household dietary diversity score. Moreover, Z-scores were used to evaluate the nutritional status of children, while body mass index was used in mothers. Results: All households suffered food insecurity, with mild food insecurity being the most prevalent (51.9%), followed by severe food insecurity (33.3%). Although all households had high diversity scores, the products they most consumed have low nutritional value, such as rice, soft drinks and oils. There was a low consumption of whole grains, fruits and vegetables. Additionally, there was a high percentage of overweight and obese mothers (57.1%) and a high prevalence of chronic undernutrition (40.9%) and global undernutrition (13.6%) in children under 5 years old. Conclusion: The predominance of severe food insecurity occurred in overweight and obese mothers with inadequate dietary diversity. This probably happened because of a lack of access to food to adequately meet the nutritional needs of each member of the family. The results suggest that health promotion with actions aimed at food security is a priority within an integral action plan for natural disasters.